Curriculum and training needs of mid-level health workers in Africa: a situational review from Kenya, Nigeria, South Africa and Uganda - Ian Couper; Sunanda Ray; Duane Blaauw; Gideon Ng'wena; Lucy Muchiri; Eren Oyungu; Akinyinka Omigbodun; Imran Morhason-Bello; Charles Ibingira; James Tumwine; Daphney Conco; Sharon Fonn (BMC, 2018)
Abstract Background Africa's health systems rely on services provided by mid-level health workers (MLWs). Investment in their training is worthwhile since they are more likely to be retained in underserved areas, require shorter training courses and are less dependent on technology and investigations in their clinical practice than physicians. Their training programs and curricula need up-dating to be relevant to their practice and to reflect advances in health professional education. This study was conducted to review the training and curricula of MLWs in Kenya, Nigeria, South Africa and Uganda, to ascertain areas for improvement. Methods Key informants from professional associations, regulatory bodies, training institutions, labour organisations and government ministries were interviewed in each country. Policy documents and training curricula were reviewed for relevant content. Feedback was provided through stakeholder and participant meetings and comments recorded. 421 District managers and 975 MLWs from urban and rural government district health facilities completed self-administered questionnaires regarding MLW training and performance. Results Qualitative data indicated commonalities in scope of practice and in training programs across the four countries, with a focus on basic diagnosis and medical treatment. Older programs tended to be more didactic in their training approach and were often lacking in resources. Significant concerns regarding skills gaps and quality of training were raised. Nevertheless, quantitative data showed that most MLWs felt their basic training was adequate for the work they do. MLWs and district managers indicated that training methods needed updating with additional skills offered. MLWs wanted their training to include more problem-solving approaches and practical procedures that could be life-saving. Conclusions MLWs are essential frontline workers in health services, not just a stop-gap. In Kenya, Nigeria and Uganda, their important role is appreciated by health service managers. At the same time, significant deficiencies in training program content and educational methodologies exist in these countries, whereas programs in South Africa appear to have benefited from their more recent origin. Improvements to training and curricula, based on international educational developments as well as the local burden of disease, will enable them to function with greater effectiveness and contribute to better quality care and outcomes.